(3OjhGf MGJe GdWGFj hCNHGQgs - (3CHhYOj MGJe Hf YHO Gddg Hf SYO Hf GdMTQL GdWGFjs
(3ChdgG (B:s
(3CNHQfG GdbGVj CHhGdbGSe Ydj Hf GdoeMSf GdJfhNj bGd(B: (3LGhQ MGJe WF aj Ref GdaSGO, hcGfJ MQH GdaSGO aj GdLGgdjI Hjf LOjdI hGdZhK s
(3BNQgG (B:s
(3boOhQj HUMQGA efUhHoI heG jfHM GdcdH CUGaqjg hEf de CLO dfRjdj pbQj bWYJ dg HYV CWQGnajg s
(3HQhGjI CHj GdefPQ gTGe Hf eMeO Hf GdSGFH GdcdHj (B204(3g``s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B173s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B69 s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI HZOGO (B- (3eYgO GdOQGSGJ GdESdGejI GdYdjG (B(227) s
Keywords: (3GdCOHs